2020
DOI: 10.1186/s12984-020-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific differences in the time-frequency representation of surface electromyographic data recorded during a submaximal cyclic back extension exercise: a promising biomarker to detect early signs of sarcopenia

Abstract: Purpose: Motivated by the goal of developing new methods to detect early signs of sarcopenia, we investigated if surface electromyographic (SEMG) data recorded during the performance of cyclic, submaximal back extensions are marked by age-specific differences in their time and frequency characteristics. Furthermore, day-today retest reliability of the EMG measures was examined. Methods: A total of 86 healthy volunteers used a back dynamometer to perform a series of three maximal voluntary contractions (MVC) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 87 publications
(129 reference statements)
2
12
0
Order By: Relevance
“…The trunk range of motion was monitored by utilizing the sagittal angular displacement data derived from a geometrical procedure, using gravity as reference, as described in previous work [ 19 , 50 ]. To calculate individual angles, the accelerometer data collected using all the probes were combined ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trunk range of motion was monitored by utilizing the sagittal angular displacement data derived from a geometrical procedure, using gravity as reference, as described in previous work [ 19 , 50 ]. To calculate individual angles, the accelerometer data collected using all the probes were combined ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We recently suggested that an index derived from surface electromyographic (SEMG) data collected during a fatigue test could be used as a digital biomarker of the elevated risk of an early onset of neuromuscular aging processes [ 18 , 19 ]. This method estimates—via a time–frequency transformations—the compression over time of the SEMG frequency spectrum associated with localized muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the data obtained by Habenicht et al [21] in their study on back extension, a diagnostic algorithm for assessing the first signs of muscle weakness related to back extension may be developed [21]. Subsequently, Gennaro et al [23], in their ES, defined "corticomuscular coherence" (CMC), obtained during locomotion by simultaneously measuring EEG and EMG, and suggested it as a new feature for the diagnosis of sarcopenia [23], reporting that it has a high sensitivity and specificity.…”
Section: Electromyographymentioning
confidence: 98%
“…After the trial, the authors concluded that dynamometer and sEMG values were highly correlated, although no statistically significant difference in muscle strength with or without sarcopenia was evidenced. On the other hand, the primary purpose of the research reported in [ 26 ] was to examine whether age-specific effects could be observed in the sEMG representation of healthy individuals engaged in cyclic back extension exercise, seeking to develop new biomarkers that could be used to screen for very early forms of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%